2011
DOI: 10.1182/blood-2010-09-307355
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and pharmacologic inactivation of cannabinoid CB1 receptor inhibits angiogenesis

Abstract: In this study we investigated the role of CB1 receptor signaling in angiogenesis and the therapeutic exploitation of CB1 inactivation as an antiangiogenic strategy. We started from the observation that CB1 receptor expression is induced during angiogenesis and that the endocannabinoid anandamide stimulated bFGFinduced angiogenesis in the nanomolar physiologic range. To define the functional involvement of CB1 receptor signaling during angiogenesis, 2 different strategies have been carried out: siRNAmediated kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 49 publications
7
55
0
Order By: Relevance
“…Our E-cadherin data also support the hypothesis that active cell migration participates in mixed islet configuration (67). As such, CB 1 R activation by both eCBs and synthetic agonists promotes the long-distance migration of neuroblasts and endothelial cells (29,30). Moreover, CB 1 Rs can signal through small GTPases, including RhoA and Rac1 in neurons (10), thus critically tuning cytoskeletal instability during neuronal morphogenesis and polarization.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our E-cadherin data also support the hypothesis that active cell migration participates in mixed islet configuration (67). As such, CB 1 R activation by both eCBs and synthetic agonists promotes the long-distance migration of neuroblasts and endothelial cells (29,30). Moreover, CB 1 Rs can signal through small GTPases, including RhoA and Rac1 in neurons (10), thus critically tuning cytoskeletal instability during neuronal morphogenesis and polarization.…”
Section: Discussionsupporting
confidence: 79%
“…This observation argues against transdifferentiation as a mechanism eliciting altered islet architecture in MAGL −/− mice. Because eCBs modulate cell migration and survival in the nervous system, adipose tissue, muscle, and immune system (13,22,(28)(29)(30)(31)(32), we instead favor that altered cell migration could, at least in part, contribute to incomplete cell segregation in MAGL −/− mice (Fig. S3).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies have examined the actions of A-EA per se in the cornea; however, it is a highly innervated tissue, and CB 1 receptors expressed on corneal sensory nerves stimulated by an agonist were found to support a role in contributing to antinociception in the anterior eye ( 47 ). Also, in a wound-healing model, both CB 1 and TRPV1 receptor activation increased proliferation and migration in corneal epithelial cells ( 48,49 ), thereby indirectly associating A-EA with these physiological functions. The presence of O-EA, ST-EA, L-EA, and DH-EA was previously unreported in corneal tissue ( 50 ).…”
Section: Analysis Of Napes In Rabbit Corneamentioning
confidence: 99%
“…S1), indicating a specific antifibrogenic activity of the CB 1 R antagonist. Recent studies also showed that CBR ligands are able to suppress the mesenteric angiogenesis in rats with liver cirrhosis and in vitro angiogenesis of endothelial cells [37,38]. …”
Section: Discussionmentioning
confidence: 99%